HUBUNGAN ANTARA MOTIVASI BELAJAR DAN KONSEP DIRI DENGAN KEMAMPUAN MENULIS NARASI PESERTA DIDIK KELAS V SEKOLAH DASAR NEGERI DI KECAMATAN PULOGADUNG ADMINITRASI JAKARTA TIMUR - Yulli Artha M; Iva Sarifah; Siti Aisyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students often experience a decline in motivation and concentration, which hinders the learning process. They also face difficulties in narrative writing, such as organizing texts, understanding stories, and using appropriate language. As a result, their writing often fails to meet the criteria for content and grammar. This study aims to determine whether learning motivation and self-concept influence students' narrative writing ability. The research was conducted at Pulogadung Cluster 1 Public Elementary Schools (binaan 1), with a total population of 466 students. The sample consisted of 215 respondents selected through probability sampling using a multi-stage sampling technique. Data collection was carried out using questionnaires. The independent variables in this study are learning motivation and self-concept, while the dependent variable is narrative writing ability. All variables were measured using a Likert scale. Data were analyzed using linear regression. Based on the standard estimation for the variables of learning motivation (X1), self-concept (X2), and narrative writing ability (Y), the structural equation is: ŷ = 0.070 + 0.513X1 + 0.519X2. The results show that learning motivation has a positive significance value of 0.513, indicating that it affects narrative writing ability; similarly, self-concept has a positive significance value of 0.519, also indicating its effect on narrative writing ability. Learning motivation and self-concept simultaneously contribute 53.1% to narrative writing ability, while the remaining 46.9% is influenced by other variables not examined in this study. Furthermore, self-concept contributes 40.1%, and learning motivation contributes 37.5% to narrative writing ability. These findings suggest that the more positive the self-concept and the higher the students' learning motivation, the better their narrative writing ability.